Sistema multiagente para monitoramento ambiental do Complexo Portuário da Ilha de São Luís-Maranhão - FARIAS, Luciana Fortes (2009)
This work is discussed the conceptual model of a multi-agent system for environmental monitoring with the use of biomarkers of aquatic organisms present in the port complex of São Luís-Maranhão-Brasil, second most important in the country in cargo handling. Located in the São Marcos Bay, this complex have an estuarine ecosystems which have suffered attacks in the current process of economic development, caused by intense port handling, dumping of ballast water and washing the vessels, overfishing, introduction of exotic species in the middle pollution in urban and industrial effluents, subject to severe environmental impacts that should be monitored. Methodologically, the modeling of the monitoring solution, we used the existing environmental conditions and aquatic life caught in two different sites of the port complex, the first in a potentially contaminated area and the second in a contamination-free (control), proposing the creation of a network of sensors in these locations. Invest conceded data by Carvalho-Neta (2007) whose research includes to catch fish in these perimeters, then submitting them for laboratory analysis to measure the enzyme activity of glutathione S-transferase (GST) and Catalase (CAT), the result was processed and recorded in bio-ontology . The core of the solution of Multi-agent system is based on the results derived from the biochemical analysis of GST, inspiring the modeling software agent that simulates the behavior of this enzyme. The solution also includes an application running on mobile devices that makes the collection of environmental variables in the selected points, validates them and makes the inference of those who could not be collected. Multi-agent System for Environmental Monitoring of the Port Complex of the Island of São Luís-Maranhão- Brasil, therefore, is made up of the bio-ontology, sensor networking, mobile application collection and inference of data from environmental conditions, software agents to simulate biochemical analysis, calculation of GST activity and other staff related to the maintenance and security of the SMA.